Short communicationLeft main aneurysm and what’s next? - Ściborski, Krzysztof; Kaaz, Konrad; Drożdż, Donald; Negrusz-Kawecka, Marta; Mysiak, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
The purpose of the case report is to present a case of a 65-year-old male, referred for coronary angiography because of a typical chest pain. The coronary angiography showed an aneurysm of the left main coronary artery. Despite the absence of obvious ischemic symptoms and because of the potential complications of the aneurysm with a width of 15 mm, the patient underwent surgery.